OP0052 Autologous Hematopoietic Stem Cell Transplantation Improves Functional Evaluation of Systemic Sclerosis Patients. (15th July 2016) - Costa Pereira, K.R.; Elias, J.; Moraes, D.; Guimarães, A.L.; Garcia, J.; Cardoso, E.; Leopoldo, V.; Zombrilli, A.; Gonçalves, E.; Costa, T.; Stracieri, A.B.; Simões, B.; et al.
Abstract : Background: Systemic sclerosis (SSc) is associated with impairment of physical function, daily life activities and quality of life. Autologous hematopoietic stem cell transplantation (AHSCT) has been investigated as treatment for patients with severe SSc, promoting reduction of skin thickening and at least stabilization of pulmonary involvement. Objectives: To evaluate the impact of AHSCT on skin involvement, functional capacity and quality of life (QoL) of SSc patients, and to compare these results with those from SSc patients under conventional immunosuppressive treatment. Methods: This is a prospective longitudinal study of a cohort of SSc patients treated at a University Hospital in Brazil. Patients treated with AHSCT (transplant group) and patients under conventional immunosuppressive treatment (control group) were evaluated before, 6 and 12 months after treatment. The evaluations included respiratory muscle strength test (maximal inspiratory pressure – MIP and maximal expiratory pressure - MEP), hand function assessments (hand-grip strength, finger-to-palm distance - FTP, COCHIN questionnaire), six-minute walk test (6MWT), modified Rodnan's skin score (mRSS) and quality of life questionnaire (SF-36). Statistical significance was established at p<0.05. Results: Nine SSc patients were included in the transplant group and 8 in the control group. When compared before, 6 and 12 months after AHSCT, patients presented improvement of MIP (p=0.0019), 6MWT distance (p=0.0459), right hand FTP (p=0.0086), right (p=0.0001) and left (p=0.0001) hand-grip strength, COCHIN (p=0.0005), mRSS (p=0.0007), and of the physical components score of SF-36 (p=0.0236). No significant differences were detected in the remaining evaluations. In the control group, no significant changes were observed 6 and 12 months after treatment at any of the evaluations. Patients from the transplant group presented better scores than those from the control group at the 6 months time point regarding MIP (p=0.0050), 6MWT distance (p=0.0418), right (p=0.0024) and left (p=0.0047) hand-grip strength, COCHIN (p=0.0088), mRSS (p=0.0272), and physical components score of SF-36 (p=0.0342). At the 12 months time point, transplanted patients presented better scores than controls concerning MIP (p=0.0242), right (p=0.0131) and left (p=0.0005) hand-grip strength, and physical components score of SF-36 (p=0.0350). Conclusions: AHSCT promotes improvement of functional capacity, skin involvement and of physical components of quality of life in SSc patients. Scores are also significantly better than those from patients treated with conventional immunosuppressive treatment. These results can be interpreted as positive outcomes of AHSCT for SSc. References: JAMA 2014;311:2490–8. Lancet 2013;381:1116–24. Disclosure of Interest: None declared